BENEFICIATION OF LATERITE IRON ORE FROM SEBUKU ISLAND, SOUTH KALIMANTAN THROUGH HEATING AND MAGNETIC SEPARATION - RAHARJO (NIM : 22114018), AGUNG
National steel consumption of Indonesia tends to increase each year in line with the increase of national economic growth. The consumption in 2013 was around 12.7 million tons in which 8.4 million tons or about 66% of the consumption were imported. On the other hand, Indonesia has abundant iron ore resources. According to the data of Indonesian Geological Resource Center in 2016, IndonesiaÃ‚Â’s iron ore resources are dominated by laterite iron ore with resource of about 2,806 million tons, whilst the primary iron ore and iron sand resources are 2,079 million tons and 18 million tons, respectively. However, laterite iron ore still contains certain amount of impurities so that research needs to be performed to improve the iron content in the ore. To increase the iron content in the ore, heating methods by both without addition of additives and with using sodium carbonate as additives then followed by process of concentration using magnetic separator were investigated. The heating experiments without additive were carried out at heating temperatures of 600, 700, 800 and 900oC, heating times of 30, 60, 90 and 120 min, grinding times with planetary ball mill of 0, 2, 4 and 6 min, and magnetic intensities of 830, 1100, 1500 and 1900 Gauss. The heating experiments with the addition of sodium carbonate as additive were carried out at heating temperatures of 900oC for 60 min and additive dosages of 3, 5, 7 and 10% sodium carbonate, grinding times with ring mill of 0.5, 1, 1.5 and 2 min and magnetic intensities of 830, 1100, 1500 and 1900 Gauss. The results of experiments showed that the ore had strong magnetic properties and it was dominated by goethite (FeOOH), hematite (Fe2O3), gibbsite (Al(OH)3) and slightly magnetite (Fe3O4). The laterite iron ore contains of 42.68% Fe and after heating increased to be 50.86% Fe. In heating process without an addition of additive followed by magnetic separation process, concentrate with Fe content of 51.12% and recovery of 96.96% was obtained. This concentrate was obtained in an optimum experimental conditions of heating temperature and time of 700oC and 30 minutes, respectively, grinding time of 4 minutes, and magnetic intensity of 1500 Gauss. With the addition of sodium carbonate as additive, concentrate with Fe content of 53.28% and recovery of 89.34% was obtained in an optimum experimental conditions of heating temperature and time 900oC and 60 minutes, respectively, sodium carbonate dosage of 7%, grinding time of 1.5 minutes and magnetic intensity of 1100 Gauss.